THE IMPORTANCE OF NAMES: A FOLLOW UP - Susan Laura Sullivan (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study aims to investigate the significance of students knowing each other’s names in fostering interpersonal communication, community, identity, and psychological safety within Japanese tertiary EFL classrooms, as well as its impact on academic and social success. Identity is both personal and social (Vignoles, 2017), and students can gain a strong sense of self when reflecting on it. Furthermore, the rapport established through the learning of names can lead to a sense of belonging (Cooper et. al, 2017). Over a two-and-a-half-year period, feedback was collected from participants in ten mandatory tertiary English courses at a Japanese university, including advanced Global Skills, advanced Reading and Writing, and intermediate Listening and Speaking classes. Drawing on U.S.-based research on identity and the use of "name tents" to enhance belonging, research focused on the effect of using mnemonics as a memory strategy for learning names in the author’s EFL classes. Establishing whether parallels from learning names existed, including any sense of belonging, was investigated. Peer to peer interaction rather than student-teacher interaction was also a main focus. Analysis revealed that a number of students felt that knowing their classmates’ names contributed to a more positive learning environment, aligning with similar findings from international studies. The study underscores the importance of name recognition in creating a supportive classroom atmosphere, indicating potential benefits for student engagement and success. This research is in its preliminary stages, with plans for a more rigorous analysis of the collected feedback to further explore the implications of name recognition on student experiences and outcomes. Considering students generally have a positive outlook towards the activity in English, its use could be considered more widely in other classroom situations.